(untitled) (Third Sector Social Economic Review, 2026)
Abstract Structural changes in traditional media, the concentration of media ownership, and the narrowing of journalistic employment have directed journalists not only toward new publishing platforms but also toward a different production model based on individual broadcasting. This study examines YouTube journalism in Turkey through the cases of Fatih Altaylı, Nevşin Mengü, and Deniz Zeyrek within the framework of “digital entrepreneurship” and “alternative media production.” The research analyzes 122 videos published between June 1 and July 31, 2025, through systematic content analysis, focusing on content management, publication rhythm, and audience engagement. Rate than describing the data only through views, likes, and comments, the study uses “view-normalized engagement” and “subscriber-normalized engagement” indicators in order to compare channels of different scales more fairly. The findings indicate that short and agenda-oriented content strategies may increase engagement intensity; however, audience loyalty cannot be explained solely by reach. The high engagement rates observed in the cases of Deniz Zeyrek and Fatih Altaylı, together with Nevşin Mengü’s longer and more explanatory publishing strategy, suggest that YouTube journalism does not follow a single model. Instead, it is shaped through different publishing rhythms, audience relations, and forms of social capital. In this respect, the study evaluates YouTube journalism not merely as an extension of political communication, but as a new media production practice shaped by platformization and metricization.